2016
DOI: 10.1080/10428194.2016.1233542
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation in elderly patients with multiple myeloma: evaluation of its safety and efficacy

Abstract: Administering high-dose chemotherapy (HDCT) with melphalan to elderly myeloma patients represents a challenge with respect to achieving therapeutic efficacy whilst avoiding significant toxicity. We analyzed safety and efficacy of HDCT in 61 elderly myeloma patients older than 65 years, including 12 patients ≥70 years, and compared them to 237 MM patients below 65 years treated in the same period. MM patients older than 70 years had a longer duration of hospitalization (26 vs. 20 days;P=.0001) and a longer time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
1
10
0
5
Order By: Relevance
“…These observations are compatible with those reported by the Centre for European Society for Blood and Marrow Transplantation, who observed that OS in 2005-2010 improved in comparison with OS in previous years in elderly transplant recipients [11]. Consistent with previous studies, we found that the age at transplantation was not significantly associated with OS [12,13,26,27]. However, several studies have reported that the age at transplantation is a risk factor of reduced OS [11,14,28].…”
Section: Discussionsupporting
confidence: 92%
“…These observations are compatible with those reported by the Centre for European Society for Blood and Marrow Transplantation, who observed that OS in 2005-2010 improved in comparison with OS in previous years in elderly transplant recipients [11]. Consistent with previous studies, we found that the age at transplantation was not significantly associated with OS [12,13,26,27]. However, several studies have reported that the age at transplantation is a risk factor of reduced OS [11,14,28].…”
Section: Discussionsupporting
confidence: 92%
“…Autologous stem cell transplantation (ASCT) after high-dose melphalan chemotherapy (HDCT) is part of the first-line standard treatment algorithm for patients with symptomatic multiple myeloma (MM) up to the age of 70 years. [1][2][3][4][5][6][7][8][9] With the incorporation of novel agents into this strategy, progression-free survival (PFS) and overall survival (OS) rates of such patients have markedly improved within the last decade. [10][11][12][13][14][15] However, almost all patients with MM will ultimately relapse at some stage following initial therapy, the majority within 3 years after ASCT, and no plateau is observed in their OS.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous stem cell transplantation (ASCT) after high‐dose melphalan chemotherapy (HDCT) is part of the first‐line standard treatment algorithm for patients with symptomatic multiple myeloma (MM) up to the age of 70 years . With the incorporation of novel agents into this strategy, progression‐free survival (PFS) and overall survival (OS) rates of such patients have markedly improved within the last decade .…”
Section: Introductionmentioning
confidence: 99%
“…65 years) were at higher risk of prolonged hospitalization 68 and post-ASCT complications (especially nonhematologic toxicities) than younger patients. 69 This, however, did not translate into a higher TRM compared with younger patients, probably because of upfront dose reductions applied in most of the studies. 65,66,68,69 A prospective, phase II study showed that bortezomib induction followed by tandem MEL (100 mg/m 2 ), ASCT, lenalidomide/prednisone consolidation, and lenalidomide maintenance was highly effective and feasible in patients age 75 or younger.…”
Section: Transplantation In Older Adult Patients With MMmentioning
confidence: 96%
“…69 This, however, did not translate into a higher TRM compared with younger patients, probably because of upfront dose reductions applied in most of the studies. 65,66,68,69 A prospective, phase II study showed that bortezomib induction followed by tandem MEL (100 mg/m 2 ), ASCT, lenalidomide/prednisone consolidation, and lenalidomide maintenance was highly effective and feasible in patients age 75 or younger. However, tandem transplant followed by consolidation and maintenance in patients older than age 70 experienced a significantly higher rate of TRM (19%) compared to younger patients (age ≤ 70, 5%).…”
Section: Transplantation In Older Adult Patients With MMmentioning
confidence: 96%